Cholesterol and desmosterol incorporation into ram sperm membrane before cryopreservation: Effects on membrane biophysical properties and sperm quality - Carro, Maria de Las Mercedes (2020)
Ram sperm are particularly sensitive to freeze-thawing mainly due to their lipid composition, limiting their use in artificial insemination programs. We evaluated the extent of cholesterol and desmosterol incorporation into ram sperm through incubation with increasing concentrations of methyl-β-cyclodextrin (MβCD)-sterol complexes, and its effect on membrane biophysical properties, membrane lateral organization and cryopreservation outcome. Sterols were effectively incorporated into the sperm membrane at 10 and 25 mM MβCD-sterols, similarly increasing membrane lipid order at physiological temperature and during temperature decrease. Differential ordering effect of sterols in ternary-mixture model membranes revealed a reduced tendency of desmosterol of segregating into ordered domains. Live cell imaging of fluorescent cholesterol showed sterol incorporation and evidenced the presence of sperm sub-populations compatible with different sterol contents and a high concentration of sterol rich-ordered domains mainly at the acrosome plasma membrane. Lateral organization of the plasma membrane, assessed by identification of GM1-related rafts, was preserved after sterol incorporation except when high levels of sterols (25 mM MβCD-desmosterol) were incorporated. Ram sperm incubation with 10 mM MβCD-sterols prior to cryopreservation in a cholesterol-free extender improved sperm quality parameters after cooling and freezing. While treatment with 10 mM MβCD-cholesterol increased sperm motility, membrane integrity and tolerance to osmotic stress after thawing, incorporation of desmosterol increased the ability of ram sperm to overcome osmotic stress. Our research provides evidence on the effective incorporation and biophysical behavior of cholesterol and desmosterol in ram sperm membranes and on their consequences in improving functional parameters of sperm after temperature decrease and freezing.